Safety analysis TMSR-500 in terms of the temperature reactivity coefficient of the fuel and the moderator using the MCNP6 software. Issue 1 (May 2021) - Manik, F R L; Suharyana,; Anwar, F; Riyatun,; Khakim, A
Abstract: TMSR-500 is a type of fourth-generation reactor that is technologically advanced with a full actinide recycling system and produces low fuel waste. This research focuses on calculating and analyzing the temperature reactivity coefficient of fuel and moderator in the TMSR-500 core designed by Martingale, Inc. All calculations performed using the MCNP6 software and the ENDF / B-VII.I continuous energy nuclear data library. The fuel material for TMSR-500 is liquid salt NaF-BeF2 -ThF4 -UF4 with enrichment of U-235 of 19.75%, and the moderator material is graphite. The variation of temperature increase in fuel and moderator starts from 293.6 K to 2500 K. As the reactor temperature increases, the value of fuel reactivity decreased, the fuel temperature reactivity coefficient is negative (-2.4879 ± 0.42) pcm/K. At the stage of calculating the moderator temperature reactivity coefficient, the calculation results show a positive value (0.0019 ± 0.0016) pcm/K as the moderator temperature increases. Based on the study of the temperature reactivity coefficient of the fuel and the moderator, then the reactor is in a safe state in terms of the overall calculation results, which indicate the total temperature reactivity coefficient is negative (-2.4883 ± 0.42) pcm/K.